Desenvolvimento de ferramentas para manipulação e geração de arquivos MIDI-SMF em linguagem funcional clean - Camargo Junior, Hélcio (2007)
One of the main goals of this work is to produce didactic material that allows a programmer or a musician to implement qualified multimedia applications by using a low level MIDI protocol and the SMF format 0 and 1. A chapter is dedicated to make clear all the concepts and solutions that involve MIDI in the polyphonic and multiinstrumental music. The author presents the underlying support for choosing a programming language adherent to the musical domain in the development of new applications using the foresaid technology. Sixteen factors led to the choice of the functional paradigm and of the language CLEAN to develop musical applications. The careful reader will also find proofs of concept for the foremost multimedia tools and techniques for developing graphical user interfaces. The work culminates in the presentation of case studies on how to use libraries for opening and analyzing MIDI files. Finally an editor for multi-timbral and polyphonic scores displays many features present only in professional tools.